1994
DOI: 10.1212/wnl.44.5.929
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between age and cognitive impairment in HIV‐1 infection

Abstract: Previous studies have identified age as a risk factor for many neurologic disorders, and a "cerebral reserve" factor has been postulated to explain these findings. This study examined whether age represents a risk factor for HIV-1-related neuropsychological dysfunction. Subjects for study 1 were primarily asymptomatic seropositive (n = 1,066) and seronegative (n = 1,004) nonelderly male community volunteers who completed neuropsychological and reaction time measures. Data analyses revealed a significant effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
43
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 0 publications
9
43
0
Order By: Relevance
“…Hence, more severe disease (lower CD4 and higher viral burden) was associated with greater BOLD signals in primarily regions that showed a greater attentional or load effect in HIV (see Fig 3). Similarly, inverse correlations between activated BOLD signals and NPZ-8 were found in several right frontal regions (inferior frontal gyrus [48,6,15 …”
Section: Correlations Between Activated Blood Oxygen Level Dependent mentioning
confidence: 82%
“…Hence, more severe disease (lower CD4 and higher viral burden) was associated with greater BOLD signals in primarily regions that showed a greater attentional or load effect in HIV (see Fig 3). Similarly, inverse correlations between activated BOLD signals and NPZ-8 were found in several right frontal regions (inferior frontal gyrus [48,6,15 …”
Section: Correlations Between Activated Blood Oxygen Level Dependent mentioning
confidence: 82%
“…CalCAP, which includes four measurements of simple reaction time (RT) and six measures of choice RT, was developed for a study of neuropsychological effects of HIV-1 infection on the CNS [27,42]. Simple and choice RT measures often are viewed as more sensitive than traditional neuropsychological tests for studying the subtle kinds of cognitive changes that may occur in the early stages of many kinds of brain disease [27].…”
Section: Methodsmentioning
confidence: 99%
“…For instance, in a large sample from the Multicenter AIDS Cohort Study (MACS) with 1,066 HIV-positive adults (mean age=35.8, SD=6.5) and 1,004 HIV-negative adults (mean age=37.3, SD=7.5), van Gorp et al (1994) found little evidence of an interaction between HIV status and age when comparing slopes of performance scores on a variety of standard neuropsychological tests and computerized reaction time tests regressed on age. Of 21 measures, only a single trend emerged, performance in executive function or attention, on the Trail Making Test Part B, became comparatively worse in the HIV-positive group (relative to the HIV-negative group) with advancing age (p=.056).…”
Section: The Interaction Between Hiv and Agingmentioning
confidence: 99%